"There`s no good, it`s just satisfactory": perfectionism, performance, and perfectionistic reactivity in NCAA student-athletes - Fleming, D. J. M.; Dorsch, T. E. (International Journal of Sport and Exercise Psychology, 2025)
Perfectionistic reactivity is a characteristic style of responding to adversity that elicits a bio-psychosocial response. Those with elevated levels of perfectionistic tendencies are thought to react disproportionately in the face of successes or failures. The present two-study paper was designed to understand the role of perfectionism in predicting season-long performance in collegiate golf while also gaining insight into NCAA student-athletes` lived experiences of perfectionism and reactivity. In Study 1, self-report measures of perfectionism were collected from 46 NCAA golf student-athletes. Tournament scores were then recorded over the NCAA`s 12-week competitive season. Data were examined using a two-level hierarchical linear model to test the moderating effect of perfectionism on student-athlete hole-over-hole performance across an entire season. In Study 2, semi-structured interviews were conducted with six student-athletes from the Study 1 sample who had self-reported high levels of perfectionistic strivings and concerns. Data were examined utilizing reflexive thematic analysis. Collectively, findings suggest that there is still work to be done to wholly understand the influence of perfectionism on sporting performance. However, athletes revealed during interviews that they experience perfectionistic reactivity through a multitude of biopsychosocial dimensions related to affect, behaviour, and cognition. Findings will allow future scholars to examine different measures of perfectionism across different performance intervals while considering the conceptual and empirical underpinnings of perfectionistic reactivity. Furthermore, future research could be designed to understand the specific circumstances under which specific thoughts, feelings, and behaviours are experienced in relation to perfectionistic reactivity.